Zero-waste process for the transformation of a hazardous aluminum waste into a raw material to obtain zeolites. (10th May 2020) - López-Delgado, Aurora; Robla, José I.; Padilla, Isabel; López-Andrés, Sol; Romero, Maximina
Abstract: A potential route to minimize the environmental impact of industrial activities is, among other approaches, the use of hazardous wastes as less-common raw materials for the preparation of other materials. Realistic technologies for waste management should include simple and low-cost processes as well as the nonproduction of new wastes. Thus, the total conversion of a type of hazardous aluminum waste into zeolite was achieved at the pilot-scale (200 l autoclave reactor) under mild hydrothermal operating conditions. In a one-step process, 3.2 tons of zeolite, 76.4 Nm 3 of ammonia and 105.9 Nm 3 of hydrogen can be produced per ton of aluminum waste. The process does not generate other wastes. The recycling of process effluents (mother liquor and rinse water), along with the process gases capture and its subsequent commercialization, would increase the environmental impact and the economic yield. The obtained Linde type-A zeolite, exhibited structural, textural and morphological characteristics similar to those of zeolites prepared from commercial reagents. A conceptual design for zero-waste process is proposed. The sustainable process developed can contribute to reduce the high environmental impact of aluminum industry waste, and contribute to the circular economy by converting a hazardous waste into a raw material. Graphical abstract: Image 1045 Highlights: Novel and simple pilot-scale process for the valorization of a hazardous Al waste. Complete transformation of a hazardous waste into a value-added material. Green and feasible process with zero-waste discharge and byproducts recovery.